Quality Culture for Preventing Technical Risk in Building Apartment Construction Project - Parura, Grace Febiola; Pamadi, Mulia; Indrastuti, Indrastuti (Civil and Sustainable Urban Engineering, 2026)
Apartment construction projects in Batam frequently encountered technical risks, such as cost overruns and schedule delays, which were exacerbated by a predominantly young workforce and stringent SLF (Certificate of Functionality) regulations. This study examined the impact of quality culture, leadership, communication, QMS, and Six Sigma on the perception of technical risk in these projects. A quantitative methodology was employed, disseminating structured online surveys to building professionals in Batam. The participants were predominantly young employees (ages 18–25) with fewer than three years of experience. Data were analyzed using descriptive statistics (percentages) and validity and reliability assessments, employing Microsoft Excel and SPSS. Most respondents (95%) agreed that a robust quality culture substantially mitigated technical risks. This favorable perception highlighted that integrating a quality culture into daily operations, including discipline and compliance with standards, was highly effective in preventing errors. Nonetheless, attitudes regarding the effectiveness of QMS, Six Sigma, and SLF were predominantly neutral, indicating a need for more consistent socialization and implementation. Technical risks originated from both physical factors and managerial procedures. A strong quality culture emerged as the key factor in reducing technical risks in apartment development projects in Batam. The construction industry needed to strengthen its quality culture, supported by modern management systems and effective communication, to ensure compliance with regulatory standards (SLF) and enhance overall project performance.